Percik-percik Pengharapan di Tengah Krisis dalam Kitab Suci - Gregorius Tri Wardoyo (Sekolah Tinggi Widya Sasana, 2021)
The phrase “history always repeats itself” seems to be appropriate to describe the events that occur in this era. Starting from this jargon, the author tries to trace the history of the Israelites, especially the histories that describe the times when they experienced a crisis in their lives. There are several points of crisis that the people of Israel experienced and amazingly they were able to get out of every crisis in their life. Behind all these, there is a God who is always with them as He promised to the ancestors of Israel and their descendants.